The Train of Thought in Horace, Epist. 2. 2. 213–216 - Keyer, Denis (Hyperboreus, 2019)
Hor. Epist. 2. 2. 214–216 (‘you have eaten, drunk and amused yourself enough; it is time for you to leave the feast of youth’) have been taken to imply: (1) leaving life (by analogy with other instances of this feast-simile in antiquity); or (2) quitting poetry and other youthful diversions in favour of studying philosophy. The latter is preferable in view of the main subject of the epistle (Horace’s excuses for dropping poetry) and structural parallels between v. 213–216 and 141–144.V. 213 (‘If you know not how to live aright, make room for the experts’) poses two problems: (1) it seems to imply giving up philosophy, whereas the preceding v. 205–212 (‘many vices are yet to be extirpated’) require the opposite sense (‘improve further’); (2) it is not clear in what way Horace’s withdrawal would make room for experts. Fr. Klingner took vivere recte in v. 213 in a hedonistic sense and interpreted decede by analogy with leaving the feast in v. 214–216. Yet, the train of thought in v. 205–212 and parallels between v. 141–144 and 213–216 suggest that vivere recte must be understood in a philosophical sense. C. M. Wieland and Ch. Brink interpret decede peritis not as a withdrawal, but only as a reverent gesture (‘respect the masters’) and deduce that it implies the necessity to learn from the experts. However, N. Rudd rightly objects that this extension from ‘respect’ to ‘respect and learn’ is illegitimate.Everything falls into place, if decedere with the dative is understood as a reverent gesture that indicates inferiority (cf. Hor. Carm. 2. 6. 15; Verg. Georg. 2. 98 assurgit): ‘If you cannot live aright, bow your head to the masters’, that is, ‘Do not imagine that you are already equal to them (and study further)’.